3D ultrasound imaging in medicine - Wang, Esther Xi (2009)
This research deals with the problem of three dimensional reconstruction from medical ultrasound images. Based on an arbitrary data set of two dimensional ultrasound images, a system has been successfully developed to reconstruct and display 3D ultrasound images. The reconstruction task involves images acquisition from ultrasound machine, image processing, data set manipulation and rendering the volume data set to display image in three-dimension.